METODA CHAID UNTUK MELIHAT FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUASAAN BAHASA INGGRIS MAHASISWA SEMESTER AKHIR STIE SWADAYA - Aziz, Azwirda (MAJALAH ILMIAH WIDYA, 2012)
It is very important to master the English as an international langguage. There are many factors which affect the studentsâ masteryof English. The CHAID method is used to study the interrelated structure between the category of mastery in English. The objectiveof this research is to get the description of mastery in English of last semester STIE Swadaya students, and to study factors affectingtheir ability in English. The results show that: (1) Most of the English mastery of last semester STIE Swadaya students are in theelementary category. (2) There is no significant difference of the English test result between the students of Accounting and Managementstudy program. (3) The most significant factors that influence the mastery in English are: (a) The understanding of English text books,(b) The English mastery of their mothers, (c) Study English in formal course, (d) The grade of the second English subject, (e) Writingin English, (f) Reading English newspapers, (g) Watching or hearing news in English, and (h) Reading comic in English.............................